ANALYSIS OF THE CONTRIBUTION OF ISLAMIC EDUCATION IN THE TIME OF THE PROPHET MUHAMMAD TO THE DEVELOPMENT OF MODERN EDUCATION - Khairan Muhammad Arif (Akademika, 2022)
Research on contributions in Education, especially in Islamic Education is very urgent for education experts and educators in the global era, especially in relation to developing the theoryof s system education. Research on the contribution of Islamic education in the time of the Prophet Muhammad saw to the development of modern Islamic Education aims to explore, introduce and implement the concepts, curriculum, learning methods and educational facilities of Islam in the time of prophet Muhammad saw and its kinbution to the development of modern education. The result of this study is that there are similarities and correlations between the concepts, objectives, curriculum and learning methods of Islamic education in the time of the Prophet and modern education, so that it can be concluded that there is a contribution of concepts, objectives and curricula as well as learning methods of Islamic education in the time of the Prophet Muhammad saw to modern education. There was a rapid development experienced by educational facilities in the time of the Prophet saw, from mosques developing rapidly in the early eighth century AD, where several mosques turned into universities until today.